A modification of tuy's algorithm for canonical dc programming problem - Toan, Nguyen Trong (Journal of Computer Science and Cybernetics, 2016)
A version of outer - approximation method is presented lor the Canonical DC optimization problem. Some computational experimens are described to compare it with other methods. Keywords. Reverse Convex Programming Canonical DC Optimization. Outer Approximation, ε-Appoximate feasible Solution.